Controlled release of 18-β-glycyrrhetic acid by nanodelivery systems increases cytotoxicity on oral carcinoma cell line. (11th May 2018) - Cacciotti, Ilaria; Chronopoulou, Laura; Palocci, Cleofe; Amalfitano, Adriana; Cantiani, Monica; Cordaro, Massimo; Lajolo, Carlo; Callà, Cinzia; Boninsegna, Alma; Lucchetti, Donatella; Gallenzi, Patrizia; Sgambato, Alessandro; et al.
Abstract: The topical treatment for oral mucosal diseases is often based on products optimized for dermatologic applications; consequently, a lower therapeutic effect may be present. 18- β -glycyrrhetic acid (GA) is extracted from Glycirrhiza glabra . The first aim of this study was to test the cytotoxicity of GA on PE/CA-PJ15 cells. The second aim was to propose and test two different delivery systems, i.e. nanoparticles and fibers, to guarantee a controlled release of GA in vitro . We used chitosan and poly(lactic-co-glycolic) acid based nanoparticles and polylactic acid fibers. We tested both delivery systems in vitro on PE/CA-PJ15 cells and on normal human gingival fibroblasts (HGFs). The morphology of GA-loaded nanoparticles (GA-NPs) and fibers (GA-FBs) was investigated by electron microscopy and dynamic light scattering; GA release kinetics was studied spectrophotometrically. MTT test was used to assess GA cytotoxicity on both cancer and normal cells. Cells were exposed to different concentrations of GA (20–500 μ mol l −1 ) administered as free GA (GA-f), and to GA-NPs or GA-FBs. ROS production was evaluated using dichlorodihydrofluorescein as a fluorescent probe. Regarding the cytotoxic effect of GA on PE/CA-PJ15 cells, the lowest TC50 value was 200 μ mol l −1 when GA was added as GA-NPs. No cytotoxic effects were observed when GA was administered to HGFs. N-acetyl Cysteine reduced mortality induced by GA-f in PE/CA-PJ15 cells. The specific effect of GA on PE/CA-PJ15 cells is mainly due to the different sensitivity of cancer cells to ROS over-production; GA-NPs and GA-FBs formulations increase, in vitro, this toxic effect on oral cancer cells.